The Feigenbaum's delta for a high dissipative bouncing ball model - Oliveira, Diego F. M. [UNESP]; Leonel, Edson Denis [UNESP] (Sociedade Brasileira de Física, 2008)
We have studied a dissipative version of a one-dimensional Fermi accelerator model. The dynamics of the model is described in terms of a two-dimensional, nonlinear area-contracting map. The dissipation is introduced via inelastic collisions of the particle with the walls and we consider the dynamics in the regime of high dissipation. For such a regime, the model exhibits a route to chaos known as period doubling and we obtain a constant along the bifurcations so called the Feigenbaum's number delta.
Keywords: Bouncing Ball Model; Dissipation; Lyapunov Exponent; Feigenbaum number